Effects of whole‐body cryotherapy (−110 °C) on proprioception and indices of muscle damage - Joseph T. Costello; L. A. Algar; Alan Donnelly (2011)
The purpose of this study was to investigate the effects of whole‐body cryotherapy (WBC) on proprioceptive function, muscle force recovery following eccentric muscle contractions and tympanic temperature ( T TY ). Thirty‐six subjects were randomly assigned to a group receiving two 3‐min treatments of −110 ± 3 °C or 15 ± 3 °C. Knee joint position sense (JPS), maximal voluntary isometric contraction (MVIC) of the knee extensors, force proprioception and T TY were recorded before, immediately after the exposure and again 15 min later. A convenience sample of 18 subjects also underwent an eccentric exercise protocol on their contralateral left leg 24 h before exposure. MVIC (left knee), peak power output (PPO) during a repeated sprint on a cycle ergometer and muscles soreness were measured pre‐, 24, 48 and 72 h post‐treatment. WBC reduced T TY , by 0.3 °C, when compared with the control group ( P <0.001). However, JPS, MVIC or force proprioception was not affected. Similarly, WBC did not effect MVIC, PPO or muscle soreness following eccentric exercise. WBC, administered 24 h after eccentric exercise, is ineffective in alleviating muscle soreness or enhancing muscle force recovery. The results of this study also indicate no increased risk of proprioceptive‐related injury following WBC.